2007
DOI: 10.1677/jme.1.02160
|View full text |Cite
|
Sign up to set email alerts
|

A conformational contribution of the luteinizing hormone–receptor ectodomain to receptor activation

Abstract: Glycoprotein hormone receptors such as the lutropin/chorionic gonadotropin receptor (LHR) are characterized by a large N-terminal ectodomain (ECD), which is responsible for hormone-receptor interactions. For the closely related TSH receptor (TSHR), it has been proposed that the ECD also serves as a tethered inverse agonist. However, the exact role of the LHR-ECD for receptor activation remains elusive. Functional analysis of N-terminally truncated LHR mutants expressed in COS-7 cells revealed that the LHR-ECD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…This possibility has been suggested in a previous report by Nishi et al (10), where the fusion of the ectodomains of LH and FSH receptors with the TMD of fly LGR2 receptor resulted in a high constitutive basal cAMP production, which could be attenuated by replacing the key residues within the exoloop-2 of the TMD with the human LHR sequences, suggesting a direct interaction of HinR with the exoloops of the TMD. However, later it was demonstrated that deletion of the entire LHR-ECD caused no significant increase in the basal cAMP production (16,17,46). Nevertheless, the present study with hFSHR and previous studies with the TSHR (7,9,11,14,15) support an activation model in which the ECD of the receptor functions as a tethered inverse agonist constraining the receptor in an inactive state.…”
Section: Constructcontrasting
confidence: 44%
See 1 more Smart Citation
“…This possibility has been suggested in a previous report by Nishi et al (10), where the fusion of the ectodomains of LH and FSH receptors with the TMD of fly LGR2 receptor resulted in a high constitutive basal cAMP production, which could be attenuated by replacing the key residues within the exoloop-2 of the TMD with the human LHR sequences, suggesting a direct interaction of HinR with the exoloops of the TMD. However, later it was demonstrated that deletion of the entire LHR-ECD caused no significant increase in the basal cAMP production (16,17,46). Nevertheless, the present study with hFSHR and previous studies with the TSHR (7,9,11,14,15) support an activation model in which the ECD of the receptor functions as a tethered inverse agonist constraining the receptor in an inactive state.…”
Section: Constructcontrasting
confidence: 44%
“…In fact, this deletion tended to reduce the LHR basal activity. Moreover, the mutationally induced constitutive receptor activation was diminished in the absence of ECD (16,17). These observations indicate specific and distinct roles for the ECDs in TSHR and LHR.…”
mentioning
confidence: 77%
“…We have shown that deletion of the entire ECD did not activate the LHR, which provokes an alternative hypothesis of an "intramolecular agonistic unit" where an internal agonist within the ECD is exposed upon ligand binding at the ECD (5, 8, 18). The latter hypothesis is supported by LHR studies showing that parts of the ECD are necessary to stabilize active state conformations of the 7TM (19,20).…”
Section: Glycoprotein Hormone Receptors (Gphrs)mentioning
confidence: 82%
“…We have shown that deletion of the entire ECD did not activate the LHR, which provokes an alternative hypothesis of an "intramolecular agonistic unit" where an internal agonist within the ECD is exposed upon ligand binding at the ECD (5, 8, 18). The latter hypothesis is supported by LHR studies showing that parts of the ECD are necessary to stabilize active state conformations of the 7TM (19,20).Here we show that all GPHRs are activated by an internal peptide sequence, which is located in the C-terminal part of the * The work was supported by the Deutsche Forschungsgemeinschaft (SSP ThyroidTransAct; BR 5108/1-1 AO 619225 and SFB/Transregio 166, project C1), the BMBF (IFB AdipositasDiseases Leipzig, FZ: 01EO1001), Interdisziplinäres Zentrum fü r Klinische Forschung (IZKF) Wü rzburg (B-281) and the University of Leipzig (Junior research grant by the Medical Faculty). …”
mentioning
confidence: 82%
“…This study supports functional-structural interrelations between different regions of the TSHR. In this respect, it has been shown several times for the TSHR that the hinge region is necessary for the stabilization of a signaling-competent basal receptor conformation (17,25,(27)(28)(29)(30)(31) and that interaction with the hormone leads to receptor activation, most probably by release of an intramolecular agonist (10,32,33).…”
mentioning
confidence: 99%